2010
DOI: 10.1002/14651858.cd006590.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Radical prostatectomy versus watchful waiting for prostate cancer

Abstract: The existing trials provide insufficient evidence to allow confident statements to be made about the relative beneficial and harmful effects of RP and WW for patients with localised prostate cancer. The results of ongoing trials should help to inform treatment decisions for men with screen-detected localised prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 146 publications
0
18
0
6
Order By: Relevance
“…Limited, high-quality randomised evidence was identified for the effect of radical treatment compared with observation in men with localised PC. A recently updated Cochrane review on prostatectomy compared with watchful waiting 146 identified only two randomised trials for inclusion: the VACURG trial, 147 which was judged to be of poor quality, and the SPCG-4 trial, 148 which was judged to be of good quality. The SPCG-4 trial, 148 carried out in Sweden, provides up to 15 years' follow-up on 695 men with localised PC randomised to either radical prostatectomy (n = 347) or watchful waiting (n = 348).…”
Section: Independent Economic Assessmentmentioning
confidence: 99%
“…Limited, high-quality randomised evidence was identified for the effect of radical treatment compared with observation in men with localised PC. A recently updated Cochrane review on prostatectomy compared with watchful waiting 146 identified only two randomised trials for inclusion: the VACURG trial, 147 which was judged to be of poor quality, and the SPCG-4 trial, 148 which was judged to be of good quality. The SPCG-4 trial, 148 carried out in Sweden, provides up to 15 years' follow-up on 695 men with localised PC randomised to either radical prostatectomy (n = 347) or watchful waiting (n = 348).…”
Section: Independent Economic Assessmentmentioning
confidence: 99%
“…Definitive treatment options mainly involve surgery (radical prostatectomy) or radiation therapy (either brachytherapy or external beam radiation) with or without androgen deprivation therapy (ADT). Other options include: active surveillance for low‐risk disease, based on an intention to intervene curatively if a change in disease character is detected with further biopsies; watchful waiting with a view to using ADT subsequently when tumour progression is determined; and ADT alone, immediately after diagnosis [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore critical that outcomes important to all stakeholders are measured and reported. However, many systematic reviews of effectiveness and clinical practice guidelines acknowledge the difficulties in synthesising the evidence base due to heterogeneity in outcome selection, definitions, measurement and reporting across different trials.…”
Section: Introductionmentioning
confidence: 99%